Progress in the development of a contactless ultrasonic processing route for alloy grain refinement. Issue 1 (May 2020) - Pericleous, K A; Beckwith, C; Bojarevics, V; Djambazov, G; Dybalska, A; Griffiths, W D; Tonry, C
Abstract: A high frequency tuned electromagnetic (EM) induction coil can be used to induce ultrasonic pressure waves leading to gas cavitation in alloy melts. This is a useful ' contactless ' approach compared to the usual immersed sonotrode technique. One then expects the same benefits obtained in the traditional ultrasonic treatment (UST) of melts, such as degassing, microstructure refinement and dispersion of particles. However, such an approach avoids melt contamination due to probe erosion prevalent in immersed sonotrodes and it has the potential to be used on higher temperature and reactive alloys. Induction stirring due to the Lorentz force produced by the coil is an added benefit, allowing for the treatment of large melt volumes, a current limitation of UST systems. At ultrasonic frequencies (> 20 kHz), due to the 'skin effect' electromagnetic forces vibrate just a thin volume by the surface of the metal facing the induction source. These vibrations are transmitted as acoustic pressure waves into the bulk and to achieve sufficient fluctuation amplitudes for cavitation, acoustic resonance is sought by carefully adjusting the generator frequency. This is akin to the tuning of a musical instrument, where the geometry and sound properties of the metal, crucible and surrounding structure play an important part. In terms of modelling, this is a multi-physics system, since fluid flow with heat transfer and phase change are coupled to electromagnetic and acoustic fields. The various models used and their coupling are explained in this paper, together with the various complications arising by the physics of cavitation. Experimental validation is obtained on a prototype rig featuring a conical induction coil inserted into the melting crucible containing the various alloys being examined. When resonance is reached, measurements demonstrate strong stirring, evidence of cavitation and finally grain refinement.